Pengaruh Pembiayaan Jual Beli, Pembiayaan Bagi Hasil Dan Non Performing Financing Terhadap Kinerja Keuangan Bank Umum Syariah (Studi Kasus Pada Bank Umum Syariah Yang Terdaftar Di Bursa Efek Indonesia 2018-2022) - Khadijah Ath Thahirah, Wafik Insani, (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2024)
This research aims to examine the influence of buying and selling financing, profit sharing financing and non-performing financing on the financial performance of Sharia commercial banks. The population of this research are companies in the Sharia Banking sector that are listed on the Indonesian Stock Exchange (BEI) for the 2018-2022 period. The sampling technique used was purposive sampling. The number of Sharia Commercial Banks sampled in this research was 11 Sharia Commercial Banks. The test tool used in this research is SPSS 21. The findings in this research show that: (1) H0 is accepted and H1 is rejected, which means that Buying and Selling Financing has no effect on the financial performance of ROA (Y) of Sharia Commercial Banks for the 2018- 2022 period. (2) H0 is accepted and H1 is rejected, which means Profit Sharing Financing has no effect on the financial performance of ROA (Y) of Sharia Commercial Banks for the 2018-2022 period. (3) H0 is accepted and H1 is rejected, which means that Non-Performing Financing has no influence on the financial performance of ROA (Y) of Sharia Commercial Banks for the 2018- 2022 period.